CHALLENGES IN UTILIZING QUIZIZZ AS A FORMATIVE E-ASSESSMENT MEDIA IN ENGLISH FOR TOUR OPERATIONS CLASS - Nova, Muhamad; Chaerunnisah, Indah Utami; Lastari, Ni Kadek Herna (Premise: Journal of English Education and Applied Linguistics, 2023)
In light of seeking the proper e-assessment media, the Quizizz application may offer some features supporting the online assessment process. However, potential issues on the obstacles faced in using the application for e-assessment have yet to be deeply investigated. The current study investigated the potential challenges in utilizing Quizizz as a formative e-assessment media in English for Tour Operations class. The current study took place in one vocational higher education. Thirty-eight vocational students were invited to participate in the study, but only 30 vocational students agreed to consent. The current study applied a qualitative approach and took a case study design. Classroom observation, questionnaire distribution, and interviews were conducted to gain the data. For the data analysis, the current study implemented three qualitative data analysis phases: reducing data, displaying data, and drawing conclusions. As a result, the current study revealed that most vocational students experienced some challenges using Quizizz during the e-assessment process. They admitted that they had internet connection problems, limited time duration, device problems, and technical skill problems. It indicated that the application could raise potential problems during the e-assessment process. During the utilization of this application, the English teacher or lecturer needs to reassure the vocational students' capacity to take the e-assessment and to offer any assistance for students facing problems during the e-assessment process.